Hegemony Da'wah Of Nahdlatul Ulama Kiai In The 2020 Regent Election: A Case Study In Semarang District - Muhyiddin, Ahmad Shofi (JURNAL TAPIS, 2023)
Kiai as a religious elite have a high "bargaining position" in winning election candidates, including in the 2020 election for the Semarang district regent. This paper discusses the hegemony da’wah of the NU kiai in Semarang district in the 2020 election for the Semarang district regent, so that it is included in the field research category using a critical qualitative approach method that is descriptive-analytic in nature using Antonio Gramsci's hegemonic theory analysis technique. The data was obtained through observation at the PCNU office in the Semarang district and two sub-districts; Bandungan and West Ungaran, which were the places for the preaching activities of the NU kiai for 3 months, from May to July 2023, by interviewing 6 informants from elements of the structural kiai, cultural kiai, PCNU officials and the general public. This research shows that the motives for the involvement of the NU kiai in the 2020 election for the Semarang district head are to fight for Islamic values that are raḥmatan lil 'ālamīn, uphold amar ma'ruf nahi munkar, and develop Islamic boarding schools. Then, the hegemony da'wah of the NU kiai in winning the candidate in the 2020 election for the Semarang district regent was realized through two parts; The first part is the process of hegemony over ordinary rural communities which is carried out through a spiritual approach. In its real form, the practice of hegemony is carried out through routine recitations or what is commonly called Naharul Ijtima'  which is held every Kliwon  Sunday. "Subjecting knowledge" is directed as a form of obedience to the preaching of the kiai in order to get blessings. The second part is educated people and NU officials. Hegemony in this section is carried out by utilizing educated community discussion forums and coordination meetings by all officials, both NU institutional officials and NU autonomous body officials at every level. The path of hegemony for educated groups and NU officials is directed more rationally by showing a good track record that has been carried out by the pair of candidates for Regent and Deputy Regent who are promoted and then associated with the science of fiqh which discusses the legal obligation to choose leaders who are just and responsible. This legal basis is then used as the theme in routine discussions every Wage Friday and coordination meetings between NU officials once a month.